Review of the genus Blitopertha Reitter, 1903 (Coleoptera: Scarabaeidae: Rutelinae) of the Caucasus and Turkey - I.V. Shokhin (Кавказский энтомологический бюллетень, 2010)
The genus Blitopertha Reitter, 1903 is presented in eastern part of its geographic areal by two species. Distribution of Blitopertha nigripennis (Reitter, 1888) is bordered by the Asian part (from Asia Minor to Kopetdagh, including the Caucasus). B. lineolata (Fischer von Waldheim, 1824) is presented by two subspecies. Distribution of nominative subspecies is bordered by SouthEastern Europe from Italy to Lower Don. A new subspecies Blitopertha lineolata vanensis ssp. n. is described from Turkey. Diagnostic character of new subspecies is double punctuation of pronotum: distance between large punctures is covered by dense punctation of small not deep points.